Anthropogenic effects on the fish fauna of River Hernád - Csipkés, Roland; Stündl, László (Acta Agraria Debreceniensis, 2015)
The fish fauna of the River Hernád was examined in 24 sampling sites in summer of 2014. As a result of the survey 31 species were detected of which eight are protected and three are highly protected by law in Hungary. The presence of the adventive tubenose goby (Proterorhinus semilunaris) in the estuary of the Hernád was observed for the first time by us. The most frequently detected species (with 100% frequency of occurrence, FO) were the chub (Squaliuscephalus), the bitterling (Rhodeusamarus) and the bleak (Alburnusalburnus), in addition the bleak was also the most dominant fish of the river. The hydraulic works have detrimental effect on the number of species and specimens and on the diversity of the fish fauna as well. The natural sections of the River Hernád have the most diverse fish assemblages.